Intelligent data engineering and automated learning - IDEAL 2011 12th international conference, Norwich, UK, September 7-9, 2011, proceedings - Yin, Hujun 1962-; Wang, Wenjia; Rayward-Smith, Victor (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Intelligent Data Engineering and Automated Learning, IDEAL 2011, held in Norwich, UK, in September 2011. The 59 revised full papers presented were carefully reviewed and selected from numerous submissions for inclusion in the book and present the latest theoretical advances and real-world applications in computational intelligence.